2022
DOI: 10.48550/arxiv.2202.04898
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nanostructured transition metal dichalcogenide multilayers for advanced nanophotonics

Abstract: Transition metal dichalcogenides (TMDs) attract significant attention due to their exceptional optical, excitonic, mechanical, and electronic properties. Nanostructured multilayer TMDs were recently shown to be highly promising for nanophotonic applications, as motivated by their exceptionally high refractive indexes and optical anisotropy. Here, we extend this vision to more sophisticated structures, such as periodic arrays of nanodisks and nanoholes, as well as proof-ofconcept waveguides and resonators. We s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…This opens a possibility of using multilayer TMDs for low-loss nanophotonics, including waveguides and high quality factor resonators. 31,45 In the visible spectral range, the imaginary parts of permittivities exhibit pronounced resonances corresponding to A-, B-, and C-excitons (Figure 3). For instance, in Figure 3, the in-plane imaginary parts of permittivities show clear A-exciton resonances at ∼676 nm (1.835 eV in MoS 2 ), ∼803 nm (1.544 eV in MoSe 2 ), ∼1167 nm (1.062 eV in MoTe 2 ), ∼629 nm (1.972 eV in WS 2 ), and ∼764 nm (1.624 eV in WSe 2 ), respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This opens a possibility of using multilayer TMDs for low-loss nanophotonics, including waveguides and high quality factor resonators. 31,45 In the visible spectral range, the imaginary parts of permittivities exhibit pronounced resonances corresponding to A-, B-, and C-excitons (Figure 3). For instance, in Figure 3, the in-plane imaginary parts of permittivities show clear A-exciton resonances at ∼676 nm (1.835 eV in MoS 2 ), ∼803 nm (1.544 eV in MoSe 2 ), ∼1167 nm (1.062 eV in MoTe 2 ), ∼629 nm (1.972 eV in WS 2 ), and ∼764 nm (1.624 eV in WSe 2 ), respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This opens a possibility of using multilayer TMDs for low-loss nanophotonics, including waveguides and high quality factor resonators. 31,45 In the visible spectral range, the imaginary parts of permittivities exhibit pronounced resonances corresponding to A-, B-, and C-excitons (Figure 3). For instance, in Figure 3, the 11,39,40,46,47 An important feature of all studied multilayer TMDs is their large birefringence Δn.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…154 However, potential applications go way beyond the field of nonlinear optics, as high refractive index by itself empowers metasurfaces for structural color generation, waveguides, photonic crystal slabs, etc. 155 Unique lattice structure of TMDCs also facilitates advanced fabrication routines with fine control over the lateral etching process. Munkhbat et al found that anisotropic wet etching using hydrogen peroxide applied to TMDs induces a self-terminating process, resulting in the formation of hexagonal structures of predefined order and complexity.…”
Section: Emerging Technologiesmentioning
confidence: 99%
“…The combination of high refractive index and strong nonlinear response driven by the excitonic nature of TMDCs already inspired several realizations of metasurfaces and nanoantennas for harmonic generation . However, potential applications go way beyond the field of nonlinear optics, as high refractive index by itself empowers metasurfaces for structural color generation, waveguides, photonic crystal slabs, etc . Unique lattice structure of TMDCs also facilitates advanced fabrication routines with fine control over the lateral etching process.…”
Section: Transition Metal Dichalcogenidesmentioning
confidence: 99%
“…This property opens a possibility of using multilayer TMDs for low-loss nanophotonics applications. 33,40 Another interesting optical feature in multilayer TMDs is their anisotropic properties due to vdW stacking nature, which results in large birefringence. Fig.…”
Section: A Uniaxial Semiconductorsmentioning
confidence: 99%